Dynamic wireless sensor networks - Oteafy, Sharief M. A.; Hassanein, Hossam S. (Hoboken : Wiley, 2014)
In this title, the authors leap into a novel paradigm of scalability and cost-effectiveness, on the basis of resource reuse. In a world with much abundance of wirelessly accessible devices, WSN deployments should capitalize on the resources already available in the region of deployment, and only augment it with the components required to meet new application requirements. However, if the required resources already exist in that region, WSN deployment converges to an assignment and scheduling scheme to accommodate for the new application given the existing resources.
6.2.2.4. Location6.2.2.5. Duty cycling; 6.2.2.6. Region of fidelity; 6.2.3. Representing applications; 6.3. Bibliography; Chapter 7: Component-Based WSNs: A Resilient Architecture; 7.1. Component-based DWSN architecture; 7.1.1. Network model; 7.1.2. Dynamic core nodes (DCN); 7.1.3. Wireless dynamic components (WDC); 7.1.4. Remote wake-up; 7.2. WDSN in operation: the synergy of dynamic sensing; 7.2.1. Operation of DWSN; 7.2.2. DCN in operation; 7.2.3. WDC in operation; 7.3. Resilience model; 7.4. Bibliography; Chapter 8: Dynamic WSNs -- Utilizing Ubiquitous Resources.
8.1. System model and assumptions.
Print version record.
Keywords: Wireless sensor networks; Technology and engineering -- Sensors; Technology and engineering -- Telecommunications; Wireless communication systems; Wireless sensor networks; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Wireless sensor networks; Electronic books